THE DETERMINANT ANALYSIS OF SERVICE QUALITY AND GOJEK'S MATCHING ALGORITHM ON THE SATISFACTION OF MUSLIMAH CUSTOMERS IN SURABAYA - Abdullah Muhammad Al-Kamal; Chetrine Alya Rinaima; Ana Toni Roby Candra Yudha; Andhy Permadi (Universitas Airlangga, 2024)
Introduction: The purpose of this study is to determine the partial influence of service quality and matching algorithm on the satisfaction of female muslim (muslimah) student customers using Gocar services in Surabaya. The research aims to investigate the effect of these two variables. The selection of a ride-hailing service catering to Muslimah-friendly preferences in Surabaya is driven by the increasing demand for such specialized services that are satisfy and safe for Muslimah. Method: Data for this research were collected through questionnaires distributed to 100 muslimah students using Gocar services in Surabaya as the research sample. Surabaya was chosen due to the high demand of this service compared to most other cities in Indonesia. The mixed-method approach involved quantitative analyses such as validity and reliability tests, classic assumption tests, t-tests, F-tests, and the coefficient of determination. Additionally, qualitative data from the interviews were analyzed to provide a comprehensive understanding of customer experiences. Results: The result is both service quality and matching algorithm have a positive impact on customer satisfaction, both individually and simultaneously. However, some criticisms were identified, such as excessive interaction from drivers that made customers uncomfortable and long waiting times for pick-up due to distant driver locations. Conclusion and suggestion: Achieving customer satisfaction is crucial for any company, including Gojek, as the provider of Gocar services. To address customer satisfaction issues, Gojek should provide training on appropriate customer interactions for drivers and improve the matching algorithm to ensure closer driver-customer proximity without relying solely on Gocar instant points.